PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus pada JNE Kota Semarang) - Utami Noor Adyati, 09.05.51.0095; Subagyo, Herry (Students Journal of Economic and Management, 2013)
Thepurpose of this study was to examine and analyze the effect of physical evidence (tangible), reliability (reliability), responsiveness (responsiveness), guarantee (assurance), and empathy (empathy) toward customer satisfaction. This type of research is explanatory research or research that is explained. The study population is people who have never used the services of Semarang JNE, samples taken 100 people. Sampling technique using purposive sampling technique based sampling certain considerations. Based on the analysis it can be concluded that: There is a positive and significant correlation between tangible, reliability, responsiveness, assurance and empathy to customer satisfaction Semarang JNE. Of the five variables, the reliability of the variables have the greatest influence, while the variable responsiveness to have the smallest effectKey words: tangible, reliability, responsiveness, assurance, empathy and customer satisfaction.